Effects of nitrogen fertilization and a commercial arbuscular mycorrhizal fungal inoculant on root rot and agronomic production of pea and lentil crops - Hubbard, Michelle; Thomson, Madeleine; Menun, Alexander; May, William E.; Peng, Gary; Bainard, Luke D. (Frontiers in Plant Science, 2023)
In the Canadian prairies, pulse crops such as field pea (Pisum sativum L.) and lentil (Lens culinaris L.) are economically important and widely grown. However, in recent years, root rot, caused by a variety of fungal and oomycete pathogens, including Aphanomyces euteiches, has become a limiting factor on yield. In this study, we examined the impacts of nitrogen (N) fertilization and a commercial arbuscular mycorrhizal fungal (AMF) inoculant on pea and lentil plant health and agronomic production at three locations in Saskatchewan: Swift Current, Indian Head and Melfort. The AMF inoculation had no impact on root rot severity, and therefore is not considered a reliable method to manage root rot in pea and lentil. In contrast, N fertilization led to reductions in root rot in Swift Current, but not the other two sites. However, N fertilization did reduce nodulation. When both pea and lentil are considered, the abundance of A. euteiches in soil increased from pre-seeding to mid-bloom. A negative correlation between soil pH and disease severity was also observed. The high between-site variability highlights the importance of testing root rot mitigation strategies under multiple soil conditions to develop site-specific recommendations. Use of N fertilizer as a root rot management strategy merits further exploration, including investigation into its interactions with other management strategies, soil properties, and costs and benefits.